Great Expectations: Migration and Labour Market Outcomes in Australia - Mitchell, W; Bill, A (My University, 2006)
It is commonly argued that higher levels of mobility among job seekers leads to greater labour market efficiency; improving job matching, reducing friction, and resulting in lower overall levels of unemployment. If unemployment gives rise to migration, and migration increases the prospect of employment (Pekkala and Tervo, 2002); labour migration might be regarded as highly micro-efficient process. In the Australian context such an argument is particularly appealing in light of flagging growth in Australia’s rural and remote regions (Mitchell and Bill, 2006).
Centre of Full Employment and Equity, the University of Newcastle, Working Paper
Keywords: Employment; Employment -- Labour mobility; Labour market; Employment and unemployment